SINYAL GEOMAGNETIK DI CEKUNGAN SENGKANG IMPLIKASI TERHADAP POLA STRUKTUR DAN KONFIGURASI BATUAN ALAS CEKUNGAN - Setyanta, Budi; Subagio, Subagio (Pusat Survei Geologi, 2013)
The intensity of magnetic anomalies at Sengkang Basin varies from -750 nTto 400 nT. Basin configuration and subsurface geological structues can be analysed by modelling of the magnetic signal of ultramafic basement. Geomagnetic analisis indicates that the Sengkang Basin is underlain by high magnetic ultrabasic rocks, and the geological structures consit of a NE-SW fold, crossedcut by a NW-SE fault. Keywords: Geomagnetic signals, Sengkang basin, ultramafic basement configuration, geological structures.